Spatial and Temporal Description of Laboratory Diagnosis of Bovine Rabies in the State of Rio Grande do Sul, Brazil - Rodenbusch, Carla Rosane; Ferreira, José Carlos; Rosa, Julio César Almeida da; Migliavacca, Victória Furtado; Bertagnolli, Angélica Cavalheiro; Peres, Michelle Elias; Almeida, Laura Lopes de (Acta Scientiae Veterinariae, 2016)
Background: Rabies remains one of the most important zoonosis worldwide and in Brazil. In the Brazilian state of Rio Grande do Sul (RS) the disease is one of the main causes of death in bovine herds. The confirmation of suspected rabies cases upon clinical examination depends on specific laboratory diagnosis. The Instituto de Pesquisas Veterinárias Desidério Finamor (IPVDF) is the reference laboratory in RS to diagnose rabies. The objective of the present study was to present a spatial-temporal description of diagnostic procedures of rabies in cattle in the years 2011 to 2015 in RS. Materials, Methods & Results: The results of diagnosis procedures of rabies in cattle carried out in the Laboratory of Virology, IPVDF, between January 2011 and December 2015 were listed. Direct immunofluorescence (DIF) and biological assays for confirming rabies cases were used. Cattle population density per area of a municipality, as well as date, species involved, location of suspected case, and diagnosis were obtained from exams and from official rabies record, and input to a spreadsheet file. Spatial distribution maps of cattle rabies confirmed in laboratory and cattle population density per municipality were constructed using the software TerraView 4.2.2 (INPE). In the study period, 998 samples of brains of cattle presenting neurological symptoms compatible with rabies, of which 582 (58%) were confirmed in the laboratory. The frequency of positive cases on a yearly basis varied between 41 and 65%, with statistically lower number of positives in 2011 (P > 0.05). The annual incidence of rabies for a population of 10,000,000 bovines was 33, 88, 112, 108, and 79, respectively, for the years 2011 to 2015, in that order. A positive correlation was observed between the number of samples analyzed and the incidence of positive cases in the study period, and statistically significant difference in incidence between years (P > 0.05). Samples were from 175 municipalities, of which 114 (65%) had at least one confirmed rabies case and 61 did not have any. The five municipalities that sent most samples for analysis were Viamão (n = 66), Montenegro (n = 40), Camaquã (n = 39), Gravataí (n = 38), and São Lourenço do Sul (n = 37). The spatial distribution of rabies in cattle in a year did not follow a defined pattern, though most cases confirmed in the laboratory occurred in the greater Porto Alegre region and in southeast RS. Discussion: High incidence of rabies was observed in 2012 and 2013, and in the two following years the number of cases confirmed in laboratory remained high, compared with 2011. The high incidence of rabies cases confirmed in laboratory correlated with the number of samples analyzed. The fall in vaccine coverage during the study period may also have prompted the increase in suspected cases and in the number of samples examined in the laboratory. A large number of the municipalities presenting rabies cases in cattle was in the greater Porto Alegre region and in southeast RS, which are areas of high and intermediate risk for the disease, according to a previous epidemiological modeling study. The spatial distribution of positive cases was not associated with the cattle population density. The large number of rabies in cattle in RS underscores the importance of the disease and the high risk of exposure, both to humans and animals. The results presented herein may help define control and prevention actions against rabies in RS.